Formulation and Evaluation of Herbal Extract of Allivum sativum (Garlic) Loaded Chitosan Nanoparticles - Gupta, Durgesh Kumari; Kesharwani, Shivangi; Sharma, N.K.; Gupta, Mahesh K. (Journal of Drug Delivery and Therapeutics, 2019)
The present study aim to get novel approach of herbal chitosan nanoparticle to get improved efficacy of the drug with a less side effect. The present study include formulation and evaluation of chitosan loaded nanoparticle of Allivum sativum by using ionic gelation method. In present study five different formulations were prepared by using the different ratio of polymer and TPP. The prepared nanoparticle was evaluated for its particle size, zeta potential, scanning electron microscopy (SEM), production yield, encapsulation efficiency (EE), stability and in-vitro drug release. The optimized Allivum sativum extract loaded chitosan nanoparticle was found with production yield of 73.59%. They were found round shape and with smooth surface. The in-vitro release profile sustained up to 90.65 %. Thus results have found F1 formulation was more stable. It showed highest in-vitro drug release. So it was found that F1 was best formulation among the all batches prepared. This formulation can be further use to treat disease like cancer.Keywords: Chitosan nanoparticle, SEM, Allivum sativum, Anti-cancer activity, Chemotherapy